Pengaruh Sampoerna Retail Community (SRC) Terhadap Daya Saing dan Pendapatan UMKM Toko Kelontong Wilayah Masbagik - Hidayat, Ardian; Riswanto, Agus (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2024)
This study aims to determine the influence of Sampoerna retail community on the competitiveness and income of UMKM grocery stores in the Masbagik area. The research method used in this study is qualitative research using a case study approach. Data sources are collected through primary data and secondary data. All SRC members who are members of the SRC Samas Cobra Riborn will be informants with a sample of 25 stores. Data collection techniques and instruments in this study use interviews, observations and documentation.Based on the results of the study, it shows that grocery stores that are members of the SRC show an increase in various aspects of competitiveness, such as improving product quality, prices, customer service and product innovation. SRC (Sampoerna Retail Community) plays a very important role in increasing income in grocery stores, because with the coaching and mentoring of these grocery stores, they have a good store management system so that they can increase grocery store income drastically like before partnering with SRC. Respondents' sales turnover is in the low category, which is below 1,000,000, while after partnering with SRC, sales turnover increased by around 2,000,000-13,000,000 and above per day